The effect of gluten-free diet on mean platelet volume levels as a short-term follow up biomarker in biopsy proven celiac disease patients and its comparison with IgA-tissue transglutaminase antibody levels - Gogra, Keerti; Beniwal, Mukesh; Patel, Palak; R. S., Ajmal; Sengar, Ghanshyam Singh; Dara, Pawan; Sharma, Neha (International Journal of Contemporary Pediatrics, 2023)
Background: Celiac disease is an autoimmune disease for which there is a known environmental trigger i.e., gluten. Adherence to gluten-free diet is the mainstay of treatment. Methods: This observational prospective study was conducted in the Department of Paediatrics, SP Medical College, Bikaner between August 2020 to August 2021. Newly diagnosed celiac disease patients below 14 years of age were included in the study excluding patients with any associated co-morbid conditions like Diabetes, Hypertension and Hypothyroidism. IgA-tTG titre and complete blood counts were performed at the time of diagnosis, and repeated after 3 months of strict gluten-free diet. The collected data were coded, tabulated and analysed. P values < 0.05 were statistically significant. Results: The mean IgA-tTG decreased from 116.28 at the time of diagnosis to 50.98 after 3 months of the gluten-free diet (p = <0.001). Also, the mean MPV decreased from 9.58 to 9.19 and the change was statistically significant (p = 0.032). When two biomarkers i.e., MPV and IgA-tTG were compared as being better biomarkers for the gluten-free diet, a weak positive correlation was observed but was not statistically significant (p = 0.212). Conclusions: This study showed that Mean Platelet Volume (MPV) levels can be used as a short-term biomarker to check adherence to the gluten-free diet.